The Impact of National Park on Catchment Communities Development: Cross River State Scenario, Nigeria - Joseph. K, Ukwayi; Eja I., Eja; E, Felix Ojong (Advances in Social Sciences Research Journal, 2015)
In recent times, the concept of National Park development has not significantly impacted on the lives of the rural communities within the area. It is on this premise that this research wishes to evaluate the impact of Cross River State National Park on catchment communities development. Three communities in Akamkpa Local Government Area were selected for this study and include Mkpot, Aking and Oban and ten percent of the projected population was used as a sampled size for the administration of questionnaires in each community. Findings indicate that most of the projects embarked upon by the Cross River State National Park were poorly executed at the same vein there was also a low level of community participation in the park management. Besides, it was noticed that the people were not provided with an alternative source of livelihood and as a result, confrontations between park management and members of host communities are frequent. Against this backdrop, much is needed to be done if effective park management and community benefits from the park must be achieved.